Medical waste generation, handling and crime statistics’ analysis in this activity field: a case study of the Poltava region (Ukraine) - Hanoshenko, Olena; Vambol, Viola; Vambol, Sergij; Yeremenko, Sergiy; Fialka, Mykhailo; Bodnar, Ihor; Inozemtseva, Oksana (Ecological Questions, 2022)
The medical waste problem has swept the whole world. Medical waste accounting and management is urgently needed to reduce the threat of the infections spread and sustainably manage environmental hazards. It is the solution of these issues on the Poltava region example that is this study purpose. Source data have been provided by the Main Department of Statistics in the Poltava region. This data is not available on the open Internet. The predictive dynamics of medical waste generation for 2010-2019 indicates a high probability of an increase in the amount of medical waste to 2030 to the volume of about 71 tons per year. The main sources are Poltava region medical institutions of which 52.3% of the total waste amount is generated in Poltava. To assess the possibility of influencing the situation with medical waste, the crime statistics in this field in the period from 2017 to 2021 was analyzed, which demonstrates an increase in offenses by more than 2.35 times. Ukrainian legislation in the field of offenses for improper handling of medical waste should be revised and articles should be developed and implemented criminal liability for offenses in this activity field.